1996
DOI: 10.1145/226643.226652
|View full text |Cite
|
Sign up to set email alerts
|

Interactive proofs and the hardness of approximating cliques

Abstract: The contribution of this paper is twofold. First, a connection is established between approximating the size of the largest clique in a graph and multi-prover interactive proofs. Second, an efficient multi-prover interactive proof for NP languages is constructed, where the verifier uses very few random bits and communication bits. Last, the connection between cliques and eftlcient multi-prover interactive proofs, is shown to yield hardness results on the complexity of approximating the size of the largest cliq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
220
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(222 citation statements)
references
References 28 publications
(27 reference statements)
1
220
0
1
Order By: Relevance
“…Garg et al showed that the problem is APX-Hard [7]. More recently, Mastrolilli et al [18] showed that the problem is NP-hard to approximate within 6 5 − ε, and that it is hard to approximate within 4 3 − ε assuming the UGC. In this work we give a tight hardness result assuming the UGC and show that the problem is hard to approximate within 2 − ε.…”
Section: Concurrent Open Shopmentioning
confidence: 99%
See 1 more Smart Citation
“…Garg et al showed that the problem is APX-Hard [7]. More recently, Mastrolilli et al [18] showed that the problem is NP-hard to approximate within 6 5 − ε, and that it is hard to approximate within 4 3 − ε assuming the UGC. In this work we give a tight hardness result assuming the UGC and show that the problem is hard to approximate within 2 − ε.…”
Section: Concurrent Open Shopmentioning
confidence: 99%
“…The techniques developed were also used to show a tight 2 − ε inapproximability result (assuming a variant of the UGC) for the classic problem of minimizing the weighted completion time with precedence constraints. They designed a PCP with one free bit, near-perfect completeness, and arbitrarily low soundness, and used the equivalence between hardness of vertex cover problem and existence of PCPs with zero free bits [6,2].…”
Section: Introductionmentioning
confidence: 99%
“…The first stage is algebraic and gives local tests for algebraic codes, usually based on multivariate polynomials. This is based on a rich collection of results on "linearity testing" or "low-degree testing" [1,3,4,5,6,7,8,9,13,14,16,17,18,20,23,25]. This first stage either yielded codes of poor rate (mapping k information symbols to codewords of length exp(k)) as in [14], or yielded codes over large alphabets as in [25].…”
Section: Introductionmentioning
confidence: 99%
“…Babai, Fortnow, Levin and Szegedy [5] showed that there exist PCPs (called holographic proofs in their result) for NP in which it is possible to verify the correctness of the proof in poly-logarithmic time. The seminal result indicating the intricate relationship between PCP systems and hardness of approximations was made by Feige, Goldwasser, LovAsz, Safra and Szegedy [12]. The definition of PCPs is implicit in their result and they show that NP C O(lognloglogn)].…”
Section: Pcps -A Brief Historymentioning
confidence: 99%